A negação dos direitos previdenciários aos camponeses do acampamento Sebastião Camargo em São Miguel do Iguaçu - PR - Depiné, Fabiana Telles David (2025)
This research aims to demonstrate the struggle of the peasants of the Sebastião Camargo Camp, located in the municipality of São Miguel do Iguaçu/PR, regarding recognition as rural producers in a family economy regime for social security purposes. The peasants in the camp of Sebastião Camargo, in addition to the struggle for land (struggle for the fair distribution of land, as provided for in the legislation that deals with agrarian reform), also seek recognition as rural producers in a family economy regime, in order to have access to social security rights. Legal recognition as rural producers in a family economy involves the recognition of the campers as agricultural producers, seeking ways to have their work activity (agricultural) recognized, which allows them to have access to the guarantee of rights denied in the not so distant past, including the social security losses that non-recognition as rural producers entails, both now and in the future. It is worth noting that, according to social security legislation, peasants, campers, workers or rural producers in a family economy regime are recognized only as rural producers. Although they have different concepts in other areas of knowledge, for the law they are the same legal subject and therefore in this research, we will treat all of them as rural producers in a family economy regime. The condition of rural producers in a family economy of the campers can be verified in their production in the small area they occupy, mainly fruit and vegetables, commercial and subsistence; as well as in their contribution (payment) to social security to guarantee their rights to benefits. However, the struggle in the sphere of legality and the guarantee of rights, such as social security, does not mean disregarding or sidelining the entire trajectory of peasant struggle and resistance in social movements such as the struggle to conquer land. In this sense, structural struggles such as the struggle for agrarian reform land go hand in hand with struggles in the sphere of the institutional order for the guarantee of legal rights, the central theme of this research. The elaboration of this research was supported by a group of authors who deal with the theme; access to documents, mainly legal and official; and field data collection (interviews and questionnaires with campers), which provided empirical support for understanding the denial, struggles and achievements of rights, in this case, social security rights for campers in Sebastião Camargo. Bibliographical, exploratory and descriptive research was carried out, in which articles and doctrines were analyzed, with a descriptive and documentary bias. The research was exploratory in nature, with the purpose of exploring all fields with the possibility of extracting the information necessary to obtain satisfactory results. The research carried out will be bibliographical research, prepared from previously published material (books, articles, theses, etc.), intensively reviewing the existing literature on a given subject in question. A questionnaire was applied by sampling (28 of the 90 families) to collect data on family composition, income, production, form of marketing of production and which benefits have been requested and denied to date. By conducting this research, we conclude that the lack of recognition as rural producers directly reflects the lack of access to social security rights, which all producers and workers who are part of Social Security have the right to access. We understand that the same problem faced by the campers at Sebastião Camargo (lack of recognition as rural producers in a family economy regime) is also present in other camps and that perhaps the methods applied to solve the problem in this camp can be disseminated and used in other camps in the country.